2014
DOI: 10.5455/ijmsph.2014.120220142
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological interpretation of endometrium in abnormal uterine bleeding

Abstract: Background: Abnormal uterine bleeding is one of the most frequent problems in life of an adult female. Accurate analysis of endometrium & localization of intrauterine lesion is the goal to effective management & better outcome of problem. Aims & Objective: To evaluate various histopathological features in D & C and/or hysterectomy in patients presenting with abnormal uterine bleeding and to find the efficacy of D & C as a better, cost effective and minimally invasive tool for screening in patients with AUB. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
11
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 17 publications
8
11
2
Order By: Relevance
“…The maximum patients were in the age group of 40-49 years (40.22%). A similar high incidence was reported by Gopalan U et al, 5 S Vaidya et al, 11 Preeti Singh et al, 12 Rupal Shah et al 13 The high incidence of AUB in this age group may be because of their climacteric period, 9 prior to the which changes occur in the ovarian-pituitary function. 15 AUB presents with different bleeding patterns.…”
Section: Of Hyperplasia Present In 88% Of Casessupporting
confidence: 77%
See 2 more Smart Citations
“…The maximum patients were in the age group of 40-49 years (40.22%). A similar high incidence was reported by Gopalan U et al, 5 S Vaidya et al, 11 Preeti Singh et al, 12 Rupal Shah et al 13 The high incidence of AUB in this age group may be because of their climacteric period, 9 prior to the which changes occur in the ovarian-pituitary function. 15 AUB presents with different bleeding patterns.…”
Section: Of Hyperplasia Present In 88% Of Casessupporting
confidence: 77%
“…24 Endometrial hyperplasias appear to be most common cause of abnormal bleeding patterns in the perimenopausal age group as they are in the climacteric period where anovulatory cycles occur causing persistent high levels of estrogen which leads to the development of hyperplasia and polyps. 13 In the present study 19.4% cases of hyperplasias were in the reproductive age group (20 -39yr).This signifies the fact that irrespective of the age group it is necessary to evaluate a case of AUB as hyperplasias are considered to be precursors of endometrial malignancy with a considerable risk of 5-10%. 8 There were no cases of polyp noted above 50yr.…”
Section: Of Hyperplasia Present In 88% Of Casesmentioning
confidence: 57%
See 1 more Smart Citation
“…There is variance with reports of other researchers where DUB was more commonly encountered in their fourth decades of life. We found a greater percentage as compared to Doraswami et al 1 , Dadhania et al 2 and R Shah et al 3 . A higher incidence than our study was reported by R Damle et al 4 and Shazia Anjum et al 5 .…”
Section: Discussioncontrasting
confidence: 40%
“…The incidence of hyperplasia in other studies were 10%, 25% and 6% with the most common age group being 41-55yrs [6,7,8]. Endometrial hyperplasia thus is most common in the perimenopausal age group [11]. Unopposed estrogen stimulation in the perimenopausal age causes endometrial proliferation & hyperplasia which in turn leads to fragile mucous membrane and irregular sloughing [2].…”
Section: Discussionmentioning
confidence: 99%